2017
DOI: 10.1039/c7dt01814b
|View full text |Cite
|
Sign up to set email alerts
|

Highly reducible π-extended copper corroles

Abstract: Di- and octa-phenylethynyl (PE) substituted π-extended copper corroles were synthesized and characterized as to their structural, electrochemical and spectroscopic properties. The addition of two or eight PE groups to the β-pyrrole positions of the corrole results in dramatic red shifts in the electronic absorption spectra and new reductions which are not seen for the parent compound lacking PE substituents. CuCor(PE) is reduced in four reversible one-electron transfer steps to give derivatives of [CuCor(PE)] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 89 publications
3
23
0
Order By: Relevance
“…Earlier electrochemical studies of cobalt corroles have often assigned the oxidation states and sites of electron transfer based on what was known for the related cobalt porphyrins, namely, cobalt­(III)/cobalt­(II), cobalt­(II)/cobalt­(I), or cobalt­(III)/cobalt­(IV) in the case of the metal-centered reactions and π-cation or π-anion radicals when the electrode reaction involves the conjugated macrocycle . However, the site of electron transfer is not so clear in the case of transition-metal corroles, which have been characterized as possessing a noninnocent macrocycle, the most-often-cited examples of which have been given for corrole derivatives containing copper or iron ions. ,,,,, …”
Section: Resultsmentioning
confidence: 99%
“…Earlier electrochemical studies of cobalt corroles have often assigned the oxidation states and sites of electron transfer based on what was known for the related cobalt porphyrins, namely, cobalt­(III)/cobalt­(II), cobalt­(II)/cobalt­(I), or cobalt­(III)/cobalt­(IV) in the case of the metal-centered reactions and π-cation or π-anion radicals when the electrode reaction involves the conjugated macrocycle . However, the site of electron transfer is not so clear in the case of transition-metal corroles, which have been characterized as possessing a noninnocent macrocycle, the most-often-cited examples of which have been given for corrole derivatives containing copper or iron ions. ,,,,, …”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical and spectroscopic properties of numerous corroles possessing a wide variety of meso - and β-pyrrole substituents have been reported over the last three decades. Many of these reports have focused on the use of these compounds for applications as redox and bioinspired catalysts or sensors, with the focal point of cobalt corrolate application involving oxygen reduction , and carbon monoxide detection. Moreover, a particular emphasis of corrole research has been placed on unveiling the electronic configuration of the molecule , to aid in the design of new catalysts . The propensity of the corrole macrocycle to behave as a noninnocent ligand under specific conditions has often hindered the ability to definitively assign an exact metal and ligand oxidation state, but published reports from our laboratory ,, and others ,,,,, have clearly demonstrated that noninnocent corrole macrocycles are significantly easier to reduce than innocent macrocyclic systems having the same formal oxidation state of the central metal ion, thus providing insights into the electronic configuration of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Both direct and indirect spectroscopic criteria, such as X-ray absorption spectroscopy (XAS), electron paramagnetic resonance spectroscopy, and UV–visible spectroscopy, laid out by Ganguly and Ghosh have been used to classify ligand noninnocence. In our own reports, we established an electrochemical litmus test, where the existence of extremely facile reductions (∼0.00 to −0.20 V vs saturated calomel electrode (SCE)) for transition-metal corroles can be used as one criterion to establish the presence of a noninnocent ligand in the case of metallocorroles with iron, cobalt, nickel, or copper. ,,, For example, in the case of cobalt triarylcorroles, the four-coordinate complexes are reduced at the macrocycle (eq ), while the six-coordinate species are reduced at the central metal ion (eq ), giving, in both cases, the same cobalt­(II) reduction product. …”
Section: Introductionmentioning
confidence: 99%
“…Both bands of Tbc compounds exhibit high extinction coefficients and on the same order of magnitude (∼10 5 L mol –1 cm –1 ). , Thus, Tbcs have the unique ability to absorb light at high intensities in two regions of the visible spectrum, both the blue and red regions. In contrast, the absorbance of corroles, a similar family of well-studied asymmetric compounds, is skewed having Soret-bands with extinction coefficients an order of magnitude higher than the Q-bands . Triazacorroles, on the other hand, have relatively matching absorbance intensities between their Soret- and Q-bands but with lower extinction coefficients relative to Tbcs …”
Section: Introductionmentioning
confidence: 99%